Evaluation of oomycete-specific fungicides and application strategies for controlling fruit rot disease on arecanut (Areca catechu L.) - Balanagouda Patil; Shankarappa Sridhara; R. Thava Prakasa Pandian; Shivaji Hausrao Thube; Nandeesha C V; Pruthviraj; Ryan Casini; Fahed A. Almana; Hosam O. Elansary (Cogent Food & Agriculture, 2024)
Phytophthora meadii causes fruit rot disease (FRD) in arecanut palm trees in the Western Ghats of Southern India. The control of this disease is challenging due to intrinsic factors like continuous rainfall, skilled climbers being required and the emergence of virulent biotypes. Farmers have been relying on the fungicides for the FRD control, however efficacy of these fungicides is largely dependent on application strategy, schedule and timings. The main aim of this investigation was to evaluate commonly used and newly developed 12 oomycete-specific fungicidal products with different application strategies in 2018 and 2019 at Malnad regions. Fungicides viz., Bordeaux mixture, Mandipropamid, Metalaxyl + Mancozeb and Fosetyl-Al were the most effective in reducing FRD and efficiently controlling (70–80%) the disease with a statistically significant difference compared to untreated control (p ≤ 0.05). However, the efficacy of the evaluated fungicides greatly varied over the years. In terms of application strategies, the pre-monsoon application proved to be more effective in controlling FRD under field conditions. Further, this study suggests that a calendar-based approach to fungicidal application is recommended for effective management of FRD.